2-(4-Hydroxyphenyl)benzothiazole dicarboxylate ester TACN chelators for 64Cu PET imaging in Alzheimer's disease. Issue 3 (24th December 2021) - Wang, Yujue; Huynh, Truc T.; Bandara, Nilantha; Cho, Hong-Jun; Rogers, Buck E.; Mirica, Liviu M.
Abstract : A series of bifunctional chelators (BFCs) with high affinity for amyloid β aggregates, a strong Cu(ii ) chelating ability, and favorable lipophilicity for potential blood–brain barrier penetration are reported. Abstract : Herein we report a new series of bifunctional chelators (BFCs) with high affinity for amyloid β aggregates, strong binding affinity towards Cu(ii ), and favorable lipophilicity for potential blood–brain barrier (BBB) penetration. The alkyl carboxylate ester pendant arms show high binding affinity towards Cu(ii ). The BFCs form stable 64 Cu-radiolabeled complexes and exhibit favorable partition coefficient (log D ) values of 0.75–0.95. Among the five compounds tested, 64 Cu-YW-1 and 64 Cu-YW-13 complexes exhibit significant staining of amyloid plaques in ex vivo autoradiography studies.